سوتیلی اولاد کے عصری مسائل اور ان کا تدارک ؛سیرتِ نبویﷺ کے تناظر میں: Contemporary problems of stepchildren and their solution; through the lens of Propheticﷺ Sirah - Akhtar, Dr. Qaria Nasreen (Al-Amīr Research Journal for Islamic Studies, 2023)
Allah Ta’ala has blessed man with countless blessings, one of which is children. A child, whether real or step-child, is a great gift from Allah. Islam is the only religion that examines the need of human society with great depth. Children, whether real or step-children, especially parents have a major responsibility to make them obedient to God. A stepfamily is a family in which at least one of the parents is not related by blood to the child. Either parent has children from a previous relationship. A stepfamily may consist of one biological mother or father, or they may spend some time with each biological mother and father. Children in stepfamilies can bond and bond with both parents, even if they live with one, it is often psychologically impossible to accept the other person’s child as their own. This happens when one’s own children are also present. There is also a strong possibility of this exploitation. On the other hand, children can also be angry with their step parents. There can be a kind of hostile environment in the family. Social and economic evils arise in the society due to the lack of proper training of the step children. The problems of love for real children and hatred for step children are interrelated, so it is very important to solve them in the context of Rabaib–e–Nabvi ﷺ. Parents should be equipped with Islamic teachings so that they do not differentiate between real and step children and educate them according to Islamic style. With this, the future of stepchildren will be characterized by high human qualities and social, economic and contemporary problems will not arise. Key words: Sirah of Holy Prophet ﷺ, Step Family, Children, Contemporary Issues.